Carbon footprint of green roof installation on school buildings in Greek Mediterranean climatic region - George Kotsiris; Andreas Androutsopoulos; Elpida Polychroni; Manolis Souliotis; Aggeliki Kavga (International Journal of Sustainable Energy, 2019)
Green roof installation in contemporary urban centres is increasing due to their numerous benefits, including microclimate improvement. However, the magnitudes of influence of the green roof design to energy savings is not fully clear, as well as the environmental benefit, in terms of reducing greenhouse gases emissions. The aim of this study was to estimate the effect of green roofs design on energy savings and their carbon footprint when installed on school buildings. The cooling and thermal insulation features of green roofs have been studied by using the TRNSYS simulation software. Different types of green roof systems (extensive and semi-intensive) and construction options are studied in four types of school buildings. Results showed that the estimated reduction in annual CO2 emissions due to energy savings and CO2 capture by plants was many times greater than the CO2 emissions that caused from roof construction.